Quantitative analysis of student satisfaction and healthcare service utilization in Philippine State universities using logistic regression - Lacida, Willie (Edelweiss Applied Science and Technology, 2025)
This study explores the relationship between university students’ satisfaction with campus healthcare services and their engagement with those services. Using a cross-sectional survey of 300 students across multiple Philippine universities, the researcher measured satisfaction (via a validated Likert-scale questionnaire) and healthcare engagement (measured as utilization of campus health services). The researcher reported high internal consistency for the satisfaction scale (Cronbach’s α = .87) and described demographic characteristics. Pearson correlation and χ² tests indicated a moderate positive association between satisfaction and engagement (r = .35, p < .001). A logistic regression (engagement as a binary outcome) was performed, controlling for age and gender; higher satisfaction significantly predicted a greater likelihood of engagement (OR = 2.48, 95% CI [1.62, 3.79], p < .001). These findings support service-quality frameworks: as expectancy–disconfirmation theory suggests, meeting students’ healthcare expectations drives satisfaction and repeated use. The results align with literature identifying care quality and staff attitude as key determinants of satisfaction. Implications include improving service quality and communication to enhance student engagement in campus health, thereby promoting well-being and academic success.